Identification of novel mutant PAX6 alleles in Indian cases of familial aniridia - Shashikanth Shetty; Vijayalakshmi Perumalsamy; Krishnadas Subbaiah; Nallathambi Jeyabalan; Neethirajan Guruswamy; Collinson Jon; Sundaresan Periasamy (BMC Ophthalmology, 2006)
Abstract Background Haploinsufficiency at the PAX6 locus causes aniridia, a panocular eye condition characterized by iris hypoplasia and a variety of other anterior and posterior eye defects leading to poor vision. This study was performed to identify novel PAX6 mutations that lead to familial aniridia in Indian patients. Methods Genomic DNA was isolated from affected individuals (clinically diagnosed aniridia) from nine unrelated aniridic pedigrees, unaffected family members, and unrelated normal controls. The coding regions of PAX6 were amplified and subjected to single strand conformation polymorphism (SSCP) gel analysis, and direct cloning and sequencing. Results SSCP band shifts, indicative of DNA base pair mutations, were observed in five of these unrelated families. Four mutations were shown to be previously unreported insertion or deletions in PAX6, leading to frameshifts. These new mutations were c.1174delTG (in exon 10), c.710delC (exon 6), c.406delTT (exon 5) and c.393insTCAGC (exon 5). The other nonsense mutation, a transition (c.1080C>T) in exon 9, has been reported previously as a mutation hotspot for PAX6 in other ethnic pedigrees. All mutant alleles transmitted through aniridic individuals in each family. Conclusion These new deletions and an insertion create frameshifts, which are predicted to introduce premature termination codons into the PAX6 reading frame. The genetic alterations carried by affected individuals are predicted to lead to loss-of-function mutations that would segregate in an autosomal dominant manner to subsequent generations. This is the first report of the 'hotspot' c.1080C>T transition from Indian families.